Plasmon resonance sensitivity in fine metal particles - Grigorchuk, N.I. (Condensed Matter Physics, 2014)
The sensitivity of the wavelength position of the surface plasmon resonances in a prolate and oblate fine metal particles to the refractive index of an embedding solution, a particle shape, and electron temperature is studied theoretically in the framework of different analytical methods. All calculations are illustrated on the single potassium nanoparticle as an example. В рамках рiзних аналiтичних методiв теоретично вивчається чутливiсть положення довжин хвилi резонансiв поверхневого плазмона у витягнутих i сплюснутих малих металевих частинках до показника
заломлення оточуючого розчину, форми самої частинки та електронної температури. Всi обчислення
проiлюстрованi на прикладi окремої наночастинки калiю.